A novel herpesvirus associated with chronic superficial keratitis and proliferative conjunctivitis in a great horned owl (Bubo virginianus). (14th April 2018) - Gleeson, Molly D.; Moore, Bret A.; Edwards, Sydney G.; Stevens, Sarah; Childress, April L.; Wellehan, James F.X.; Robertson, Jessica; Murphy, Christopher J.; Hawkins, Michelle G.; Paul‐Murphy, Joanne
Abstract: An adult great‐horned owl ( Bubo virginianus; GHOW ) presented with a history of recurrent corneal ulceration of the right eye (OD). Findings included ulcerative superficial keratitis, proliferative conjunctivitis, and iris pigmentary changes. The ulcer was initially nonresponsive to medical therapy, but showed rapid and appropriate healing following diamond burr debridement. Proliferative conjunctivitis markedly improved following topical antiviral therapy with cidofovir 1%, interferon alpha 2B ophthalmic solutions, and orall ‐lysine. Histopathologic evaluation of a conjunctival biopsy revealed epithelial features suspicious for viral cytopathic changes and intranuclear structures suspicious for viral inclusions, suggestive of a possible viral‐induced papillomatous conjunctivitis. A novel alphaherpesvirus, referred to as Strigid Herpesvirus 1 (StrHV1), was identified using PCR and gene sequencing. This case represents a new clinical manifestation of a previously unreported herpesvirus in the GHOW. Identification of the herpes virus was critical to administration of appropriate therapy and resolution of the conjunctivitis, and corneal epithelial debridement promoted resolution of the chronic corneal epithelial defect.